Answer:
1
When second polarizer is removed the intensity after it passes through the stack is
![I_f_3 = 27.57 W/cm^2](https://tex.z-dn.net/?f=I_f_3%20%3D%2027.57%20W%2Fcm%5E2)
2 When third polarizer is removed the intensity after it passes through the stack is
![I_f_2 = 102.24 W/cm^2](https://tex.z-dn.net/?f=I_f_2%20%3D%20102.24%20W%2Fcm%5E2)
Explanation:
From the question we are told that
The angle of the second polarizing to the first is
The angle of the third polarizing to the first is ![\theta_3 = 61^o](https://tex.z-dn.net/?f=%5Ctheta_3%20%3D%2061%5Eo)
The unpolarized light after it pass through the polarizing stack ![I_u = 60 W/cm^2](https://tex.z-dn.net/?f=I_u%20%3D%2060%20W%2Fcm%5E2)
Let the initial intensity of the beam of light before polarization be ![I_p](https://tex.z-dn.net/?f=I_p)
Generally when the unpolarized light passes through the first polarizing filter the intensity of light that emerges is mathematically evaluated as
![I_1 = \frac{I_p}{2}](https://tex.z-dn.net/?f=I_1%20%3D%20%5Cfrac%7BI_p%7D%7B2%7D)
Now according to Malus’ law the intensity of light that would emerge from the second polarizing filter is mathematically represented as
![I_2 = I_1 cos^2 \theta_1](https://tex.z-dn.net/?f=I_2%20%3D%20I_1%20cos%5E2%20%5Ctheta_1)
![= \frac{I_p}{2} cos ^2 \theta_1](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7BI_p%7D%7B2%7D%20cos%20%5E2%20%5Ctheta_1)
The intensity of light that will emerge from the third filter is mathematically represented as
![I_3 = I_2 cos^2(\theta_2 - \theta_1 )](https://tex.z-dn.net/?f=I_3%20%3D%20I_2%20cos%5E2%28%5Ctheta_2%20-%20%5Ctheta_1%20%29)
![I_3= \frac{I_p}{2}(cos^2 \theta_1)[cos^2(\theta_2 - \theta_1)]](https://tex.z-dn.net/?f=I_3%3D%20%5Cfrac%7BI_p%7D%7B2%7D%28cos%5E2%20%5Ctheta_1%29%5Bcos%5E2%28%5Ctheta_2%20-%20%5Ctheta_1%29%5D)
making
the subject of the formula
![I_p = \frac{2L_3}{(cos^2 \theta [cos^2 (\theta_2 - \theta_1)])}](https://tex.z-dn.net/?f=I_p%20%3D%20%5Cfrac%7B2L_3%7D%7B%28cos%5E2%20%5Ctheta%20%5Bcos%5E2%20%28%5Ctheta_2%20-%20%5Ctheta_1%29%5D%29%7D)
Note that
as
is the last emerging intensity of light after it has pass through the polarizing stack
Substituting values
![I_p = \frac{2 * 60 }{(cos^2(21) [cos^2 (61-21)])}](https://tex.z-dn.net/?f=I_p%20%3D%20%5Cfrac%7B2%20%2A%2060%20%7D%7B%28cos%5E2%2821%29%20%5Bcos%5E2%20%2861-21%29%5D%29%7D)
![I_p = \frac{2 * 60 }{(cos^2(21) [cos^2 (40)])}](https://tex.z-dn.net/?f=I_p%20%3D%20%5Cfrac%7B2%20%2A%2060%20%7D%7B%28cos%5E2%2821%29%20%5Bcos%5E2%20%2840%29%5D%29%7D)
![=234.622W/cm^2](https://tex.z-dn.net/?f=%3D234.622W%2Fcm%5E2)
When the second is removed the third polarizer becomes the second and final polarizer so the intensity of light would be mathematically evaluated as
![I_f_3 = \frac{I_p}{2} cos ^2 \theta_2](https://tex.z-dn.net/?f=I_f_3%20%3D%20%5Cfrac%7BI_p%7D%7B2%7D%20cos%20%5E2%20%5Ctheta_2)
is the intensity of the light emerging from the stack
substituting values
![I_f_3 = \frac{234.622}{2} * cos^2(61)](https://tex.z-dn.net/?f=I_f_3%20%3D%20%5Cfrac%7B234.622%7D%7B2%7D%20%2A%20cos%5E2%2861%29)
![I_f_3 = 27.57 W/cm^2](https://tex.z-dn.net/?f=I_f_3%20%3D%2027.57%20W%2Fcm%5E2)
When the third polarizer is removed the second polarizer becomes the
the final polarizer and the intensity of light emerging from the stack would be
![I_f_2 = \frac{I_p}{2} cos ^2 \theta_1](https://tex.z-dn.net/?f=I_f_2%20%3D%20%5Cfrac%7BI_p%7D%7B2%7D%20cos%20%5E2%20%5Ctheta_1)
is the intensity of the light emerging from the stack
Substituting values
![I_f_2 = \frac{234.622}{2} cos^2 (21)](https://tex.z-dn.net/?f=I_f_2%20%3D%20%20%5Cfrac%7B234.622%7D%7B2%7D%20cos%5E2%20%2821%29)
![I_f_2 = 102.24 W/cm^2](https://tex.z-dn.net/?f=I_f_2%20%3D%20102.24%20W%2Fcm%5E2)